IMPORTANCE OF ELECTORAL RIGHTS AND ISSUES OF THEIR PROTECTION (Journal of actual problems of jurisprudence, 2020)
Abstract. The right to vote is one of the most important rights of citizens of the Republic, allowingthem to participate in the management of state affairs, in the formation of the highest echelon of powerby the people. The article is devoted to the study of the protection of citizens’ electoral rights and theirimportance. The article deals with the electoral law as a form of participation of citizens in the managementof state affairs, its constitutional and legal consolidation, the place and role of the institution ofelections in the functioning of the state, the constitutional basis for the protection of electoral rights ofcitizens in the Republic of Kazakhstan. The article considered main causes of violations of electoral rightswere identify and ways to protect them were identified. In States that affirm the true popular community,voting rights recognize the most accessible and often used constitutional possibility of citizen interferencein state and local power, direct participation of citizens in the state and local issues. However, theconstitutional and legal consolidation of the suffrage as a form of participation of the population in themanagement of state affairs does not provide a full basis for determining the democratic nature of thestate. The elected rights of citizens in state-legal instruments are not only enshrined, but in real termscan be observed the formal, realistic nature of the democracy of any state, if they have found and implementedtheir action in real terms Life.Key words: democracy, the right to vote, source of state power, democratic state, protection ofelectoral rights.